Changes in the Bacteriome of Honey Bees Associated with the Parasite Varroa destructor, and Pathogens Nosema and Lotmaria passim - Hubert, Jan; Bičianová, Martina; Ledvinka, Ondřej; Kamler, Martin; Lester, Philip J; Nesvorná, Marta; Kopecký, Jan; Erban, Tomáš (Microbial ecology, 2017)
The honey bee, Apis mellifera, is a globally important species that suffers from a variety of pathogens and parasites. These parasites and pathogens may have sublethal effects on their bee hosts via an array of mechanisms, including through a change in symbiotic bacterial taxa. Our aim was to assess the influence of four globally widespread parasites and pathogens on the honey bee bacteriome. We examined the effects of the ectoparasitic mite Varroa destructor, the fungal pathogens Nosema apis and Nosema ceranae, and the trypanosome Lotmaria passim. Varroa was detected by acaricidal treatment, Nosema and L. passim by PCR, and the bacteriome using MiSeq 16S rRNA gene sequencing. Overall, the 1,858,850 obtained sequences formed 86 operational taxonomic units (OTUs) at 3 % dissimilarity. Location, time of year, and degree of infestation by Varroa had significant effects on the composition of the bacteriome of honey bee workers. Based on statistical correlations, we found varroosis more important factor than N. ceranae, N. apis, and L. passim infestation influencing the honey bee bacteriome and contributing to the changes in the composition of the bacterial community in adult bees. At the population level, Varroa appeared to modify 20 OTUs. In the colonies with high Varroa infestation levels (varroosis), the relative abundance of the bacteria Bartonella apis and Lactobacillus apis decreased. In contrast, an increase in relative abundance was observed for several taxa including Lactobacillus helsingborgensis, Lactobacillus mellis, Commensalibacter intestini, and Snodgrassella alvi. The results showed that the "normal" bacterial community is altered by eukaryotic parasites as well as displaying temporal changes and changes associated with the geographical origin of the beehive.
Keywords: Nosema; Animals; RNA, Ribosomal, 16S; včely; infestace roztoči; Varroidae; mikrobiota; Mite Infestations; symbióza; zvířata; Lactobacillus; Microbiota; Symbiosis; Kinetoplastida; RNA ribozomální 16S; Bees; Bartonella